POST-DIGITAL PRACTICE AND SPATIAL SPECIFICITY OF MUSIC - Ryabinina, Olena; Trynyak, Maya; Kovalenko, Inna; Kalnytsyi, Eduard; Kharlamov, Mykhailo (Revista Inclusiones, 2020)
The specificity of space aesthetics in virtual music is analyzed in the article, we consider the basic features of Homo Virtualis as a unity formed by effect of accessible Infinite and apperception of mostly affective-bodily experience. Hermeneutic potential of Homo Virtualis is provided by uniformed coding of sound qualities inside the digital continuum, transformed shapes of conceptual art. Sound performance of the open is embodied not only through the allusions of Ambient but refined post-digital aesthetics, aesthetics of ‘failure’, methods of ‘glitch’. Implementing philosophical and aesthetical tools we investigate ideology and practice of virtual music-making. Digital artists experience is considered via microsound technology, tele-immersion, as a version of post-digital with orientation on a myth of nature. It is shown that evocation of music and sound unity of Homo Virtualis reveal/bring to life ancient views about magic of the soundscape. Simultaneously, through ontological self-sufficiency of τέχνη in online music the fact that post-digital aesthetics belongs to the digital appears in hypostasis from aesthetical music being into impersonal media-message. Mutual representation of the truth and mystification which is specific to art is transforming into performed myth of involvement. Virtual music causes speculations on essence and limits of music